Transanal total mesorectal excision for restorative coloproctectomy in an obese high-risk patient with colitis-associated carcinoma. Issue 3 (4th May 2017) - Hanke, Laura Isabel; Bartsch, Fabian; Försch, Sebastian; Heid, Florian; Lang, Hauke; Kneist, Werner
Abstract: Transanal total mesorectal excision (TaTME) offers great potential for the treatment of malign and benign diseases. However, laparoscopic-assisted TaTME in ulcerative colitis has not been described in more than a handful of patients. We present a 47-year-old highly comorbid female patient with an ulcerative colitis–associated carcinoma of the ascending colon and steroid- refractory pancolitis. A two-stage restorative coloproctectomy including right-sided complete mesocolic excision was conducted. The second step consisted of a successful nerve-sparing TaTME and a handsewn ileal pouch–anal anastomosis. TaTME may extend the possible treatment options in inflammatory bowel disease, especially for high-risk patients.